Sea fever - Peyton, K.M. (New York : The World Publishing Company, 1962)
After his father is drowned, 15-year-old Matt Pullen must earn money to buy a fishing boat which he needs to earn a living for a family of five
Keywords: England -- Juvenile fiction; Fisheries -- Fiction; Sea stories